Investigation The Exergy Performance of a Forced Draft Wet Cooling Tower - Abdulrazzaq Kareem, Fadhil; Al-Dulaimi, Mustafa; Samir Lafta, Noor (International Journal of Engineering and Technology, 2018)
The performance of a forced draft wet cooling tower was investigated experimentally and the calculation was performed by applying second law of thermodynamics (exergy analysis). The mathematical model was developed by using engineering equation solver (EES) software. The results show that the chemical exergy of air increases from the bottom to the top of the cooling tower, the thermal exergy of air decreases from bottom to the top of the cooling, the exergy of water decreases from top to the bottom of the cooling tower. The exergy destruction decreases from bottom to the top of the cooling tower, and the exergy efficiency decreases from top to the bottom of the cooling. The exergy destruction tends to increase as the inlet wet bulb temperature increases while the exergy efficiency decreases. As water-air flow rate ratio increases the exergy destruction increases while the exergy efficiency decreases. The results show that there is an inverse proportional be-tween exergy destruction and exergy efficiency. Â Â